Recurrent posterior shoulder instability starting in childhood and adolescence: is it worth stabilizing shoulders in voluntary instability becoming involuntary and uncontrollable?. (1st December 2020) - Langlais, Tristan; Hardy, Marie B.; Lavoue, Vincent; Barret, Hugo; Wilson, Adam; Boileau, Pascal
Abstract : Aims: We aimed to address the question on whether there is a place for shoulder stabilization surgery in patients who had voluntary posterior instability starting in childhood and adolescence, and later becoming involuntary and uncontrollable. Methods: Consecutive patients who had an operation for recurrent posterior instability before the age of 18 years were studied retrospectively. All patients had failed conservative treatment for at least six months prior to surgery; and no patients had psychiatric disorders. Two groups were identified and compared: voluntary posterior instability starting in childhood which became uncontrollable and involuntary (group VBI); and involuntary posterior instability (group I). Patients were reviewed and assessed at least two years after surgery by two examiners. Results: In all 38 patients (40 shoulders) were included: group I (20 shoulders), with involuntary posterior instability (onset at 14 years of age (SD 2.3), and group VBI (20 shoulders), with initially voluntary posterior instability (onset at 9 years of age (SD 2.6) later becoming involuntary (16 years of age (SD 3.5). Mean age at surgery was 20 years (SD 4.6 years; 12 to 35). A posterior bone block was performed in 18 patients and a posterior capsular shift in 22. The mean follow-up was 7.7 years (2 to 18). Recurrence of posterior instability was seen in nine patients, 30% in group VBI (6/20 shoulders) and 15% in group I (3/20 shoulders) (p > 0.050). At final follow-up, the shoulder's of two patients in each group had been revised. No differences between either group were found for functional outcomes, return to sport, subjective, and radiological results. Conclusion: Although achieving stability in patients with so-called voluntary instability, which evolves into an involuntary condition, is difficult, shoulder stabilization may be undertaken with similar outcomes to those patients treated surgically for involuntary instability. Cite this article: Bone Joint J 2020;102-B(12):1760–1766.